Terrorist Offences under Polish Law - Rosicki, Remigiusz (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2023)
The material scope of the research problem encompasses issues concerned with the essence and sense of the legal definition of a terrorist offence in the Polish criminal law. The Polish legislator implemented the definition of a terrorist offence under Art. 115 § 20 of the Criminal Code in 2014, which was caused by the necessity to align the Polish law with the EU regulations. Metaphorically, it needs to be recognised that the definition in a way modifies the prohibited act and the scope of criminal liability. The structure of the legal definition of a terrorist offence comprises two elements, which serve as conditions to be fulfilled by the perpetrator. The first condition is formal and concerned with the severity of the sanction apportion to the perpetrator’s main act, while the second condition is motivational and concerned with a special goal actuating the perpetrator. Undoubtedly, the institution of the terrorist offence in the Polish criminal law serves a dissuasive and repressive purpose in relation to perpetrators of such offences. In order to elaborate the objective scope of the analysis, the following research questions are presented in the paper: (1) To what degree is the legal definition of a terrorist offence effective in the criminal policy regarding prevention and combating terrorism? (2) To what degree may the content of the legal definition of a terrorist offence infringe the principle of nullum crimen sine lege certa? The analysis is an overview, and has been performed considering an institutional and legal approach. In this approach, textual, doctrinal, and functional interpretations have been applied to the content of the legal definition of a terrorist offence. Given the discrepancies arising from the ambiguity of the terms used in the definition, relatively great emphasis has been laid on linguistic interpretation.

Zakres przedmiotowy problemu badawczego prezentowanego w tekście obejmuje kwestie związane z istotą i sensem definicji legalnej przestępstwa o charakterze terrorystycznym w polskim prawie karnym. Polski ustawodawca zaimplementował definicję przestępstwa o charakterze terrorystycznym w ramach art. 115 § 20 Kodeksu karnego w 2014 roku, co wynikało z konieczności dostosowania polskiego prawa do regulacji Unii Europejskiej. Stosując metaforę uznać należy, że definicja ta stanowi swoisty rodzaj modyfikatora czynu zabronionego i zakresu odpowiedzialności karnej. Struktura definicji legalnej przestępstwa o charakterze terrorystycznym skalda się z dwóch elementów, będących zarazem przesłankami, które wypełnić ma sprawca. Pierwsza przesłanka ma charakter formalny, i dotyczy wysokości sankcji przypisanej głównemu czynowi sprawcy, z kolei druga przesłanka ma charakter motywacyjny, i dotyczy szczególnego rodzaju celu, jaki przyświeca w działaniu sprawcy. Niewątpliwie instytucja przestępstwa o charakterze terrorystycznym w polskim prawie karnym pełni funkcje odstraszającą i represyjną w stosunku do sprawców tego typu przestępstw. W celu uszczegółowienia zakresu przedmiotowego podjętej analizy w tekście przedstawiono następujące pytania badawcze: (1) W jakim stopniu definicja legalna przestępstwa o charakterze terrorystycznym jest efektywna w polityce karnej w zakresie przeciwdziałania i zwalczania zjawiska terroryzmu?, (2) W jakim stopniu treść definicji legalnej przestępstwa o charakterze terrorystycznym może naruszać zasadę nullum crimen sine lege certa? Analiza zawarta w tekście ma głównie charakter poglądowy, w ramach, którego wykorzystano ujęcie instytucjonalno-prawne. W ramach tego ujęcia treść definicji legalnej przestępstwa o charakterze terrorystycznym poddano interpretacji tekstualnej, doktrynalnej i funkcjonalnej. W związku z rozbieżnościami wynikającymi z niejednoznaczności terminów użytych w tej definicji stosunkowo duży nacisk położono na interpretację językową.
Przestępstwa o charakterze terrorystycznym w polskim prawie
Keywords: counter terrorism security; terrorism; terrorist offence; combating terrorism; penal policy; bezpieczeństwo antyterrorystyczne; terroryzm; przestępstwo o charakterze terrorystycznym; zwalczanie terroryzmu; polityka karna